Effect of Digital Device on Computer Vision Syndrome: Meta-Analysis - Asri Wahyu Azzahro; Bhisma Murti; Eti Poncorini Pamungkasari (Journal of Epidemiology and Public Health, 2023)
Background: Computers are an integral part of today's modern human life, where long-term use can cause complaints of visual disturbances. Eye complaints related to computer use are called computer vision syndrome. This study aims to determine the magnitude of the influence of the use of digital screens or devices on the occurrence of computer vision syndrome with meta-analysis.Subjects and Method: The meta-analysis was carried out using the PRISMA flowchart and the PICO Population: students model. Intervention: the duration of using the digital screen is long. Comparison: the duration of using the digital screen is short. Outcome: the incidence of computer vision syndrome. The databases used are PubMed, ScienceDirect, Web of Science, Cochrane library, Google Scholar and CINAHL with keywords (Computers OR Handheld OR Mobile Devices OR “Digital Device” OR Digital Screen) AND (Asthenopia OR “Computer Vision Syndrome” OR Eye Strain OR Digital Eye Strain) AND (“Students” OR School Children OR Secondary Children OR Postgraduate Students). The inclusion criteria in this study were full text articles with a cross-sectional design for 2018 to 2022 in English. The article was then critically reviewed using the Prisma flow chart diagram and analyzed with RevMan 5.3.Results: Meta-analysis was conducted on 9 articles with a cross-sectional study design originating from Ghana, Saudi Arabia, Ethiopia, Spain, Thailand, Lebanon and China involving 28,888 students. The results of the meta-analysis show that the long duration of digital device use increases the risk of experiencing CVS by 2.31 times compared to the short duration of digital device use (aOR= 2.31; 95% CI= 1.60 to 3.32; p<0.001).Conclusion: The duration of using digital devices has a higher risk of experiencing Computer Vision Syndrome. Keywords: Student, Digital Device, Computer Vision Syndrome, Meta-Analysis Correspondence: Asri Wahyu Azzahro. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: asriwahyuazzahro@gmail.com. Mobile: +6281328543318.